The Role of Social Services in Improving the Welfare of Poor Communities in Takalar District - Sakawati, Herlina; Azhari, Megawati; Sulmiah, Sulmiah (Jurnal Aktor, 2023)
This paper aims to find out how the role of the Social Service in Improving the Welfare of the Poor in Takalar Regency and what Supporting and Inhibiting Factors are encountered in optimizing it.  Using a qualitative approach, data collection was carried out through observation, interviews and documentation techniques.  The data analysis technique used is interactive data analysis through the stages of: data collection, data reduction, data analysis, and conclusion testing.  The results of this study indicate that the role of the Social Service in Improving the Welfare of the Poor in Takalar Regency is based on several indicators: 1.  Stabilizers that have not gone well, because the realization of social assistance programs for the poor has not been evenly distributed, 2. Innovators that are running well, due to new innovations from social services as a form of service that can help collect data on the poor effectively, 3.  Modernizers that have been going well, this can be seen from the impact of the program provided to the community which is very helpful in meeting the daily needs of the poor, 4. Pioneers that have not gone well, because there is no form of derivative services from the social services themselves that can provide  a form of pioneering that has a positive impact on society, 5. The executor himself has not gone well, this is because there is no form of cooperation between social services and other agencies as a form of cooperation in tackling the poor.